Drivers of halal orientation strategy among halal food firms - Zailani, S.; Kanapathy, K.; Iranmanesh, M.; Tieman, M. (Emerald, 2015)
Purpose - The purpose of this paper is to investigate the factors that motivate the halal food firms in Malaysia to practice halal orientation strategy (HOS). Design/methodology/approach - Data were obtained from a survey of 137 halal food firms in Malaysia, and analyzed using the partial least squares technique. Findings - Results showed that halal market demand, government support, expected business benefits, and integrity positively affect HOS. Practical implications - The findings of the study will help policy makers and managers of halal food firms to understand external and internal drivers of HOS, which may lead to successfully motivating the implementation of HOS in halal food firms. Originality/value - Although HOS plays a key role in protecting the halal status of any given product, this topic is rarely explored. This study thus contributes to the advancement of knowledge on factors that motivate the halal food firms to practice HOS.